2012
DOI: 10.1007/s00246-012-0400-y
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil and Ventriculo-Arterial Coupling in Fontan-Palliated Patients: A Noninvasive Echocardiographic Assessment

Abstract: The fundamental role of pulmonary vascular resistance in the Fontan circulation is obvious. Medications decreasing this resistance may have an impact on the fate of this population. Hence, we assessed noninvasively the effect of oral sildenafil on the ventriculo-arterial coupling in patients with Fontan circulation. In a single-center, prospective case series study, 23 patients with fenestrated extracardiac total cavopulmonary connection age 12-31 years were enrolled in this study. Clinical characteristics and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…The other coupling studies in Fontan patients used similar methods as ours or even much simplified, less‐rigorous methods, but did not include similarly studied non‐Fontan patients to determine whether VA parameters were abnormal relative to persons without Fontan circulation 30, 31. A mathematical simulation study and an animal study of acute Fontan physiology indicated that immediately after creation of a Fontan circulation, Ees is mildly reduced whereas Ea is increased 24, 32.…”
Section: Discussionmentioning
confidence: 99%
“…The other coupling studies in Fontan patients used similar methods as ours or even much simplified, less‐rigorous methods, but did not include similarly studied non‐Fontan patients to determine whether VA parameters were abnormal relative to persons without Fontan circulation 30, 31. A mathematical simulation study and an animal study of acute Fontan physiology indicated that immediately after creation of a Fontan circulation, Ees is mildly reduced whereas Ea is increased 24, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies were based on high level of endothelin-1 in Fontan patients9,10), the endothelin receptor antagonist induced improvement of clinical, hemodynamic parameters and exercise capacity. Experiences with sildenafil therapy on Fontan patients have also been reported11,12). In a recent study, Rhodes et al15) reported on the effect of inhaled iloprost on exercise function of Fontan patients.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies8,9,10,11,12) reported the pulmonary vasodilating therapy had an effective influence on Fontan patients so we want to determine whether inhaled iloprost as a pulmonary vasodilator might have a role in the clinical symptoms, hemodynamics and exercise capacity of Fontan patients.…”
Section: Introductionmentioning
confidence: 99%
“…12 To use these measures more routinely, single beat estimations of echocardiographic Ees and Ea (ie, estimates of Ees and Ea that do not require load alteration to be measured) have been developed and validated in children. 4,13 Ea was calculated as (0.9 × systolic blood pressure/stroke volume). Ees was calculated as (0.9 × systolic blood pressure/end-systolic volume).…”
Section: Methodsmentioning
confidence: 99%